THE WELFARE OF GRABBIKE DRIVERS WHO USE BPJS KETENAGAKERJAAN IN THE PERSPECTIVE OF MAQASHID AL SYARIAH - Pratiwi, Eka Aprila; Anggraini, Tuti; Muhaisin, Ahmad (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2022)
The transportation services in Indonesia have undergone rapid changes in the past decade. However, the welfare of Grabbike drivers using BPJS Ketenagakerjaan in Medan remains an issue. This study aims to analyze the welfare of Grabbike drivers from the perspective of maqashid al syariah. The research method used is qualitative descriptive, focusing on the income of Grabbike and traditional ojek services in Medan, with several Grabbike passengers as subjects. Primary data was obtained through interviews with Grabbike drivers and customers in Medan, while secondary data was sourced from books and e-journals related to BPJS Ketenagakerjaan. Data collection techniques included observation, interviews, and literature review. The findings indicate that the welfare of Grabbike drivers using BPJS Ketenagakerjaan can be enhanced by meeting basic needs, reducing difficulties, and improving the quality of life. This aligns with maqashid al syariah, which emphasizes the welfare and well-being of all individuals.